Penggunaan Media Pembelajaran Berbasis Blog untuk Membangkitkan Motivasi Siswa Kelas IX dalam Menulis Cerpen - Hariyani Hariyani (Publikasi Indonesia, 2022)
Expressing experiences and ideas in the form of short stories by paying attention to the structure and language is a basic competency that must be mastered by students in grade IX SMP/MTs. In reality, the motivation of grade IX students in writing short stories is very low. This can be seen from the number of students who submit assignments and the quality of the short stories produced. This condition is a challenge for teachers to find the problems that cause it and find the right solution to overcome the problem. Through the teacher's personal blog that presents short story models that are in accordance with the level of psychological development of students and close to students, it is hoped that it can arouse students' motivation in reading and writing short stories.